Treatment Delays in Primarily Resected Oropharyngeal Squamous Cell Carcinoma: National Benchmarks and Survival Associations. (December 2018) - Morse, Elliot; Judson, Benjamin; Husain, Zain; Burtness, Barbara; Yarbrough, Wendell G.; Sasaki, Clarence; Cheraghlou, Shayan; Mehra, Saral
Objective: To characterize treatment delays in surgically treated oropharyngeal cancer, identify factors associated with delays, and associate delays with survival. Study Design: Retrospective cross-sectional analysis. Setting: Commission on Cancer–accredited institutions. Subjects and Methods: We identified patients in the National Cancer Database with surgically treated oropharyngeal cancer. We characterized the durations of diagnosis-to-treatment initiation, surgery-to-radiation treatment, radiation treatment duration, total treatment package, and diagnosis-to-treatment end intervals as medians. We associated delays with patient, tumor, and treatment factors via multivariable logistic regression analysis and with overall survival by Cox proportional hazards regression. Results: In total, 3708 patients met inclusion criteria. Median durations of diagnosis-to-treatment initiation, surgery-to-radiation treatment, radiation treatment duration, total treatment package, and diagnosis-to-treatment end intervals were 27, 42, 47, 90, and 106 days, respectively. Medicaid and human papillomavirus (HPV) negativity were associated with delays. Delayed total treatment package and diagnosis-to-treatment end intervals were associated with decreased survival (hazard ratio [HR] = 1.81 [1.29-2.54], P = .001 and HR = 1.97 [1.39-2.78], P < .001, respectively); this was maintained following HPV stratification. Delays in the surgery-to-radiation treatment interval were associated with decreased overall survival in HPV-negative but not HPV-positive patients (HR = 2.05 [1.19-3.52], P = .010 and HR = 1.15 [0.74-1.80], P = .535, respectively). Diagnosis-to-treatment initiation and radiation treatment duration were not associated with overall survival in the overall cohort (HR = 1.21 [0.86-1.72], P = .280 and HR = 1.40 [0.99-1.99], P = .061, respectively); however, following stratification, delayed radiation treatment duration approached significance in HPV-negative but not HPV-positive patients (HR = 1.60 [0.96-2.68], P = .072 and HR = 1.35 [0.84-2.18], P = .220). Conclusion: Treatment durations identified here can serve as national benchmarks and for institutions to compare quality to their peers. Distinct benchmarks should be applied to HPV-negative and HPV-positive patients.